Fungi from Malus in Qujing, China: two new species, three new records, and insights into potential host jumping and lifestyle switching - Zhang, Gui-Qing; Li, Zhu-Mei; Fan, Xin-Lei; Li, Qi-Rui; Kumla, Jaturong; Suwannarach, Nakarin; Elgorban, Abdallah M.; Moussa, Ihab M.; Dai, Dong-Qin; Wijayawardene, Nalin N. (Frontiers in Cellular and Infection Microbiology, 2025)
Apple trees [Malus domestica Borkh. (Rosaceae)] are one of the important temperate fruit crops in China. In comparison to other temperate fruits, such as grapes and pears, fungal studies (in Yunnan) associated with M. domestica are fewer in number. In the present study, we investigated fungi associated with M. domestica in Qujing City, Yunnan Province, China. Samples were collected from apple gardens in different locations. Single spore isolation was carried out to isolate saprobic fungi, while the surface sterilization method was carried out to isolate endophytic fungi. Molecular analyses were carried out to determine the phylogenetic placement of the new collections. Based on the combined methods of morphology and phylogeny, Cytospora qujingensis sp. nov. and Hypoxylon malongense sp. nov. are introduced as novel saprobic and endophytic taxa, respectively. Moreover, Aureobasidium pullulans and Cytospora schulzeri are reported as new geological records from southwestern China. Allocryptovalsa castaneae is reported on M. domestica in China for the first time. The checklist of fungi associated with M. domestica in China is presented.